The ROY Family's Growing Palette: Insights Into Recent Compound Additions and Color Range Expansion - A Short Review - Nogueira, Bernardo A.; FAUSTO, RUI (Elsevier, 2024)
The ROY (systematic name: 5-methyl-2-[(2-nitrophenyl)amino]-3-thiophene-carbonitrile) molecule family stands as the most renowned group of color polymorphic organic compounds. This article offers a concise overview of the main structural characteristics of the 13 known polymorphs of ROY, systematizing their diverse colors in a context where recent data (2022-2024) obtained for novel members of the family are also taken into account, in particular information extracted from our own studies on AcROY, ROY-ol and ROY-CAM. The new findings have extended the spectrum of ROY-based polymorphs' colors to include burgundy and, notably, green tones.
Keywords: AcROY; Color Polymorphism; FuROY; ROY; ROY-CAM; ROY-ol